2019 Florida Blueberry Integrated Pest Management Guide - Jeffrey G. Williamson; Philip F. Harmon; Oscar E. Liburd; Peter Dittmar (EDIS, 2018)
This 38-page publication provides current information on pest, disease, and weed management, and plant growth regulator use for commercial blueberries in Florida. It is a minor revision written by Jeffrey G. Williamson, Philip F. Harmon, Oscar E. Liburd, and Peter Dittmar, and published by the Horticultural Sciences Department, September 2018.